Dominance relationships in Syrian hamsters modulate neuroendocrine and behavioral responses to social stress. (2nd November 2018) - Dulka, Brooke N.; Koul-Tiwari, Richa; Grizzell, J. Alex; Harvey, Marquinta L.; Datta, Subimal; Cooper, Matthew A.
Abstract: Stress is a well-known risk factor for psychopathology and rodent models of social defeat have strong face, etiological, construct and predictive validity for these conditions. Syrian hamsters are highly aggressive and territorial, but after an acute social defeat experience they become submissive and no longer defend their home territory, even from a smaller, non-aggressive intruder. This defeat-induced change in social behavior is called conditioned defeat (CD). We have shown that dominant hamsters show increased neural activity in the ventromedial prefrontal cortex (vmPFC) following social defeat stress and exhibit a reduced CD response at social interaction testing compared to subordinates. Although the vmPFC can inhibit the neuroendocrine stress response, it is unknown whether dominants and subordinates differ in stress-induced activity of the extended hypothalamic-pituitary-adrenal (HPA) axis. Here, we show that, following acute social defeat, dominants exhibit decreased submissive and defensive behavior compared to subordinates but do not differ from subordinates or social status controls (SSCs) in defeat-induced cortisol concentrations. Furthermore, both dominants and SSCs show greater corticotropin-releasing hormone (CRH) mRNA expression in the basolateral/central amygdala compared to subordinates, while there was no effect of social status on CRH mRNA expression in the paraventricular nucleus of the hypothalamus or bed nucleus of the stria terminalis. Overall, status-dependent differences in the CD response do not appear linked to changes in stress-induced cortisol concentrations or CRH gene expression, which is consistent with the view that stress resilience is not a lack of a physiological stress response but the addition of stress coping mechanisms. Lay summary: Dominant hamsters show resistance to the behavioral effects of acute social defeat compared to subordinates, but it is unclear whether social status modulates the neuroendocrine stress response in Syrian hamsters. This study indicates that dominant social status does not alter stress-induced activity of the extended hypothalamic-pituitary-adrenal (HPA) axis, which suggests that the ability of dominants to cope with social defeat stress is not associated with changes in their neuroendocrine stress response.